A generalized relation between the local values of temperature and the corresponding heat flux in a one-dimensional semi-infinite domain with the moving boundary - Kulish, Vladimir. (2012)
The paper presents generalized relation between the local values of temperature and the corresponding heat flux in a onedimensional